Pharmacokinetics and distribution of minocydine in different biological fluids of goats after intravenous administration - Jayachandran, C; Singh, M K; Singh, S D; Jha, H N (The Indian Journal of Animal Sciences, 2012)
Pharmacokinetics and distribution of minocycline in different biological fluids were carried out after a single iv dose @ 5 mg/kg. Peak concentrations of 3.51±0.27, 5.00±0.39 and 85.69±3.67µg/kg. mg/ml were obtained at 1 hr in interstitial fluid (I S F), milk and urine, respectively. Distribution half life (t½α) of 1.24 ± 0.13 hr and elimination half life (t½β) of 7.27 ± 0.30 hr were observed in goat in the present study. Vd area of 3.11 ± 0.34 L/kg obtained for minocycline in goat denotes its wide distribution in the body. The calculated loading dose (D*) and maintenance dose (D) for maintaining MIC of 0.5µg/ml at the dosage interval (γ) of 12 hr were 6.9 ± 0.6 and 4.7 ± 0.4 mg/kg.